Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas I SD Bahrul Ulum Surabaya - Taseman; Akhmad; Aulia Puspita; Della Puspita Sari (BADA'A: Jurnal Ilmiah Pendidikan Dasar, 2021)
The purpose of this study was to improve the initial reading ability of the first graders of SD Bahrul Ulum Surabaya. This research is a research using descriptive qualitative method that uses the type of research observation and interviews which then the results are analyzed descriptively. The results of this study are the steps for applying the SAS method to grade 1 students at SD Bahrul Ulum Surabaya and examples. The application of the SAS method is useful for improving the reading ability of the first graders of SD Bahrul Ulum Surabaya. The application of the SAS method is the best method in improving the ability of beginning reading skills, but in this case the teacher is required to be creative, skilled, and patient.